Genocide And Crimes Against Humanity Under The Rome Statute - عجوب هبة (Latakia University Journal - Economic and Legal Sciences Series, 2022)
The 20th century was a time of extreme violence. Throughout it, several large-scale massacres had been committed in different parts of the world, in which the lives of millions of innocent people had been taken. The thing that prompted the international community to criminalize the grave acts that shook the conscience of humanity and threatened the security and safety of states, referring to them as "international crimes" that were limited to the four crimes listed in the Rome Statute that established the International Criminal Court. Among these four crimes, genocide and crimes against humanity have been given international status regardless of whether they were committed during a period of peace or conflict. While these two crimes vary in some respects, they overlap in others, creating a kind of confusion for national courts and even international criminal courts. Therefore, this article focuses on outlining the main points that distinguish each of these crimes.